TINGKAT KEPUASAN LAYANAN CUSTUMER SERVICE BERDASARKAN METODE WEBQUAL 4.0 PADA PT TRITANA DENGAN PLS-SEM - Andi Arfian; Dede Mustomi; Juarni Siregar; Adelia Alvi Yana (Journal of Information System, Informatics and Computing, 2021)
In the world of business, especially for service businesses, there are many strategies to make a business successful. In addition to a reliable marketing strategy, a business also needs excellent service so that it can make consumers comfortable and happy. Each company will compete to provide the best service for its customers which makes customers satisfied so that it can improve other aspects such as sales, profit. In this study the authors analyzed aspects of the web service service available at PT Tratana, namely by analyzing the excellent service system to consumers with Using the Webqual4 model and data processing with the Pls-Sem method from the results of this study it is expected to know the extent to which the effectiveness and satisfaction of consumers after buying the products they buy from the analysis results obtained by many variables that are not significant to customer satisfaction..